Of some peculiarities of generalized rheological body. 2 - Ye. Bytzan (Геофизический журнал, 2014)
Peculiarities of high-rank rheological bodies (RB) formation through unification of two RBs with lesser number of elements were analyzed. The necessary and sufficient conditions for the nonsingularity of complex RB are formulated, which lie in the equality of difference between the quantity of parallel and consecutive connections in the formed RB to one, and the RB relaxation times that are composed in case of parallel connections and aftereffect times in case of consecutive connection were different. The function of relaxation creeping were built, with the help of which the cores are built, as well as resolutions of integral equations of the 2nd kind, which describe nonelastic processes in media with aftereffects.